(untitled) (NAU Journal of Library and Information Science, 2021)
This study investigated challenges in the selection and acquisition of grey literature in Nigerian Libraries. Five research questions guided the study. Survey research design was adopted for the study. Population of the study comprised 17 staff working in Chukwuemeka Odumegwu Ojukwu University Library, Igbariam Campus. There was no sampling because the population of the study was small and manageable. The instrument used for data collection was questionnaire. Mean and frequency tables were used to analyse the research questions. The major findings of the study showed that all categories of grey literature resources were available in the library studied and that grey literature was acquired through purchase, donation and exchange. Major challenges libraries face in the acquisition of grey literature was paucity of funds. Based on the findings, it was recommended that government should increase the funding for the acquisition of grey literature in university libraries. It was also recommended that the library management should embark on regular review and supply of new and more grey materials. It was further recommended that the library management should employ subject specialists to assist in the selection acquisition of grey materials. The study further recommended that the library management should create proper awareness to both teachers and students on the importance of grey literature in education.